Improvement of Mathematics About Plane Figures Through Realistic Mathematics Education (RME) Approach With Concrete Materials To Fourth Grade Students of SDN Karangrejo In Academic Year Of 2019/2020 - Rakai Paksi Hinu Sadhewo; Wahyudi Wahyudi; Ratna Hidayah (Universitas Sebelas Maret, 2020)
Abstract: Improvement of Mathematics About Plane Figures Through Realistic Mathematics Education (RME) Approach With Concrete Materials To Fourth Grade Students of SDN Karangrejo In Academic Year Of 2019/2020. The study aimed: (1) to describe the step of RME approach with concrete materials, (2) to improve mathematics, and (3) to describe obstacle and solution. It was a collaborative classroom action research carried out in three cycles. The subjects were teachers and students. Data collection techniques were observation, interviews, and tests. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results showed that: (1) the steps to the application of RME approach with concrete materials were understanding contextual problems with concrete materials, explaining contextual problems with concrete materials, solving contextual problems with concrete materials, comparing and discussing answers, also drawing conclusion; (2) the RME approach with concrete materials improved mathematics about plane figures. It was proven by the increasing of mastery learning: 87.50% in the first cycle, 90.62% in the second cycle, and 93, 75% in the third cycle; (3) the obstacles were: the teacher did not use concrete materials when presenting contextual problems, there were a few students asking questions, the students were less active in responding the results of discussion, the students were less conducive during discussion, the tecaher drew the conclusion. The solutions were the teacher used concrete materials, the teacher gave motivation to the students to ask questions, the teacher encouraged the students to respond to each other during presentation, the teacher kept the students enganged in a group, and the teacher guided the students to summarize the results of the discussion.